Associations of Smoking and Age With Inflammatory Joint Signs Among Unaffected First‐Degree Relatives of Rheumatoid Arthritis Patients: Results From Studies of the Etiology of Rheumatoid Arthritis. Issue 8 (27th July 2016) - Sparks, Jeffrey A.; Chang, Shun‐Chiao; Deane, Kevin D.; Gan, Ryan W.; Kristen Demoruelle, M.; Feser, Marie L.; Moss, LauraKay; Buckner, Jane H.; Keating, Richard M.; Costenbader, Karen H.; Gregersen, Peter K.; Weisman, Michael H.; et al.
Abstract : Objective: To examine whether genetic, environmental, and serologic rheumatoid arthritis (RA) risk factors are associated with inflammatory joint signs in a cohort of first‐degree relatives (FDRs) of RA patients. Methods: We evaluated RA risk factors and inflammatory joint signs in a prospective cohort of FDRs without RA in the Studies of the Etiology of RA. Genetic factors included 5 HLA–DRB1 shared epitope alleles and 45 RA‐associated single‐nucleotide polymorphisms; loci were combined using genetic risk scores weighted by RA risk. Environmental factors (smoking, body mass index, education, and parity) and RA‐related autoantibodies were assessed at baseline. Physical examination was performed at baseline and 2‐year follow‐up, by observers who were blinded with regard to autoantibody status, to assess inflammatory joint signs as tender or swollen joints at sites typical for RA. Logistic regression was performed to evaluate associations of genetic, environmental, and serologic factors with inflammatory joint signs. Results: We analyzed 966 non‐Hispanic white FDRs at baseline and 262 at 2‐year follow‐up after excluding those with inflammatory joint signs at baseline. The mean ± SD age was 47.2 ± 15.5 years, 71% were female, and 55% were shared epitope positive. Smoking >10 pack‐years was associated with inflammatory joint signs at baseline (odds ratio [OR] 1.89 [95% confidence interval (95% CI) 1.26–2.82]) and at 2 years (OR 2.66 [95% CI 1.01–7.03]), compared to never smokers. There was a significant interaction between smoking and age with regard to risk of inflammatory joint signs ( P  = 0.02). FDRs younger than 50 years with >10 pack‐years had the highest risk of inflammatory joint signs (OR 4.39 [95% CI 2.22–8.66], compared to never smokers younger than 50 years). Conclusion: In a high‐risk cohort of FDRs, smoking and age were associated with both prevalent and incident inflammatory joint signs at sites typical for RA. Further prospective investigations of the factors affecting the transitions between preclinical RA phases are warranted.